Knock-out of CD73 delays the onset of HR-negative breast cancer by reprogramming lipid metabolism and is associated with increased tumor mutational burden - Paweł Kamil Serafin; Marta Popęda; Kamila Bulak; Agata Zwara; Barbara Galikowska-Bogut; Anna Przychodzka; Adriana Mika; Tomasz Śledziński; Marcin Stanisławowski; Kamila Jendernalik; Marika Bolcewicz; Wiktoria Laprus; et al. (Elsevier, 2024)
Objective: CD73 (ecto-5'-nucleotidase, NT5E), a cell-surface enzyme converting 5'-AMP to adenosine, is crucial for cancer progression. However, its role in the tumorigenesis process remains mostly obscure. We aimed to demonstrate CD73's role in breast cancer (BC) tumorigenesis through metabolic rewiring of fatty acid metabolism, a process recently indicated to be regulated by BC major prognostic markers, hormone receptors (HR) for estrogen (ER), and progesterone (PR). Methods: A murine model of chemically induced mammary gland tumorigenesis was applied to analyze CD73 knock-out (KO)-induced changes at the transcriptome (RNA-seq), proteome (IHC, WB), and lipidome (GC-EI-MS) levels. CD73 KO-induced changes were correlated with scRNA-seq and bulk RNA-seq data for human breast tissues and BCs from public collections and confirmed at the proteome level with IHC or WB analysis of BC tissue microarrays and cell lines. Results: CD73 KO delayed the onset of HR/PR-negative mammary tumors in a murine model. This delay correlated with increased expression of genes related to biosynthesis and β-oxidation of fatty acids (FAs) in the CD73 KO group at the initiation stage. STRING analysis based on RNA-seq data indicated an interplay between CD73 KO, up-regulated expression of PR-coding gene, and DEGs involved in FA metabolism, with PPARγ, a main regulator of FA synthesis, as a main connective node. In epithelial cells of mammary glands, PPARγ expression correlated with CD73 at the RNA level. With cancer progression, CD73 KO increased the levels of PUFAn3/6 (polyunsaturated omega 3/6 FAs), known ligands of PPARγ and target for lipid peroxidation, which may lead to oxidative DNA damage. It correlated with the downregulation of genes involved in cellular stress response (Mlh1, Gsta3), PR-or CD73-dependent changes in the intracellular ROS levels and expression or activation of proteins involved in DNA repair or oxidative stress response in mammary tumor or human BC cell lines, increased tumor mutational burden (TMB) and genomic instability markers in CD73 low HR-negative human BCs, and the prolonged onset of tumors in the CD73 KO HR/PR-negative group. Conclusions: CD73 has a significant role in tumorigenesis driving the reprogramming of lipid metabolism through the regulatory loop with PR and PPARγ in epithelial cells of mammary glands. Low CD73 expression/CD73 KO might enhance mutational burden by disrupting this regulatory loop, delaying the onset of HR-negative tumors. Our results support combining therapy targeting the CD73-adenosine axis and tumor lipidome against HR-negative tumors, especially at their earliest developmental stage.